Estructura poblacional de Pinus radiata D.Don en fragmentos de Bosque Maulino en Chile central - GÓMEZ, PERSY; BUSTAMANTE, RAMIRO; SAN MARTÍN, JOSÉ; HAHN, STEFFEN (Gayana Botánica, 2011)
In this note we examine the population structure of Pinus radiata, exotic plant that is invading fragments of the Maulino Forest. We evaluate pine density, age, proportion of reproductive individuals across 8 forest fragments. Our results indicate a high proportion of young individuals and reproductive individuals growing inside fragments. Moreover, the fragment size is negatively correlated with pine density but, the proportion of reproductive individuals are not correlated with this landscape attribute. Our result indicate the existence of a pine population that is actively invading forest fragments, a fact that needs to be considered in conservation plans of this native forest.